Kajian Hadis tentang Korupsi: Studi Takhrij dan Syarah - Andika Firja Tulloh (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the hadith about corruption. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about corruption in the history of Abu Daud No. 3109. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi fulfills the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Abu Daud no. 3109 is relevant to be used as motivation, fighting spirit, and lessons to eradicate corruption starting from the environment itself.